Gastronomia afetiva, comunica????o e transforma????o - Riccetto, Luli Neri (2016)
This paper aims at analyzing gastronomy as a non-verbal communication process and the relations established through cooking and eating together. It is assumed that a bond is created between cook and diner and that there is a discourse between them, being the food the mediator of several possible kinds of relations. Thus, emotional relations arising from these proceedings are investigated, inquiring the proposed notion: affective gastronomy. In order to work this object, experiments were performed and show that communication through gastronomy is able to affect relations. my as a non-verbal communication process and the relations established through cooking and eating togeA brief theoretical review on the peculiar relation established between human beings and food is carried out, as well as communication as an event and phenomenon that initially involves the body. The concept of ???affection??? as an important aspect of communication is investigated as proposed by Cyrulnik and Maffesoli. The notion of met??poro as defended by Ciro Marcondes is applied to bring all these aspects together. It is believed that gastronomic language is demonstrated by displays of affection.